Kepatuhan Wajib Pajak Kendaraan Bermotor pada Unit Pengelolaan Pendapatan Daerah Kabupaten Rembang - Audrye, Winda; Suryarini, Trisni (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the effect of mobile samsat, e-samsat, tax sanctions, tax socialization, and taxpayer awareness on taxpayer compliance in Rembang Regency partially and simultaneously. The sampling method uses an accidental sampling technique and the number of samples obtained using the Solvin formula is 100 respondents. The data analysis technique uses descriptive statistical analysis, classical assumption test (normality test, multicollinearity test, and heteroscedasticity test), and multiple linear regression analysis (t statistical test and f statistical test) processed with SPSS Statistic 26. The results showed that mobile samsat, tax socialization, and taxpayer awareness positively and significantly affected taxpayer compliance. In contrast, e- samsat and tax sanctions did not affect taxpayer compliance. Keywords: compliance, awareness, samsat, sanctions, outreach